Human Pancreatic Cancer-Associated Stellate Cells Remain Activated after in vivo Chemoradiation - Cabrera, M. Carla; Tilahun, Estifanos; Nakles, Rebecca; Diaz-Cruz, Edgar S.; Charabaty, Aline; Suy, Simeng; Jackson, Patrick; Ley, Lisa; Slack, Rebecca; Jha, Reena; Collins, Sean P.; Haddad, Nadim; et al. (Frontiers in Oncology, 2014)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by an extensive fibrotic reaction or desmoplasia and complex involvement of the surrounding tumor microenvironment. Pancreatic stellate cells are a key mediator of the pancreatic matrix and they promote progression and invasion of pancreatic cancer by increasing cell proliferation and offering protection against therapeutic interventions. Our study utilizes human tumor-derived pancreatic stellate cells (HTPSCs) isolated from fine needle aspirates of pancreatic cancer tissue from patients with locally advanced, unresectable pancreatic adenocarcinoma before and after treatment with full dose gemcitabine plus concurrent hypo-fractionated stereotactic radiosurgery. We show that HTPSCs survive in vivo chemotherapy and radiotherapy treatment and display a more activated phenotype post therapy. These data support the idea that stellate cells play an essential role in supporting and promoting pancreatic cancer and further research is needed to develop novel treatments targeting the pancreatic tumor microenvironment.